Muslim Women in Austria and Germany Doing and Undoing Gender Making Gender Differences and Hierarchies Relevant or Irrelevant - Volkmann, Constanze; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2019)
Constanze Volkmann develops an innovative new gender theory labeled doing and undoing gender. Based on empirical findings she examines the highly debated intersection of gender and Islam. The analysis of interviews with various Muslim women unravels the many different ways in which gender is done and undone. Especially with regard to potential gender hierarchies, the results reveal that the category 'gender' is irrelevant to many Muslim women and is even used as a means to foster their status and power as women. This book makes a substantial contribution to a differentiated social debate at eye level with Muslim women. Contents • Muslim Population in Austria and Germany: Its Origins, Current Contexts and Definitional Challenges • Integrating Previous Theoretical Perspectives: A Comprehensive Approach to Gender • Different Types of Doing and Undoing Gender with Regard to Income-Generating Work • Different Types ofDoing and Undoing Gender with Regard to Motherhood Target Groups • Lecturers and students of sociology, psychology, gender studies, education and social anthropology • Actors from the fields of journalism, politics (ministries, offices, police), in hospitals, schools, counseling centers The Author Dr. Constanze Volkmann is assistant professor at the Competence Center for Empirical Research Methods at the Vienna University of Economics and Business, Austria. Her areas of expertise include qualitative research methods as well as gender theory and research.
Muslim Population in Austria and Germany: Its Origins, Current Contexts and Definitional Challenges -- Integrating Previous Theoretical Perspectives: A Comprehensive Approach to Gender -- Different Types of Doing and Undoing Gender with Regard to Income-Generating Work -- Different Types of Doing and Undoing Gender with Regard to Motherhood.
Keywords: Feminism; Feminist theory; Culture; Culture -- Study and teaching; Feminism and Feminist Theory; Sociology of Culture; Cultural Studies